Effectiveness of stiffeners on steel plate shear buckling at ambient and elevated temperatures. (15th February 2019) - Glassman, Jonathan D.; Boyce, Veronica; Garlock, Maria E. Moreyra
Highlights: A stiffener on the compression diagonal increases the postbuckling shear strength. The most important role of a stiffener is providing lateral restraint. At ambient temperature, the axial force in the stiffener is negligibly small. At 700 °C, the axial force in the stiffener is up to 35% of the shear strength. Abstract: There are a growing number of bridge fire events and the National Fire Protection Association (NFPA) requires that critical structural elements of the bridge be protected from elevated temperatures due to fire. However, no guidance is given on how to protect these critical elements, nor how to identify them. Further, slender steel web plates have been shown to be vulnerable to shear buckling in fire events and recent research that indicates that the load path of shear forces in thin web plates is not well understood. The overall objective of this paper is to examine the effectiveness of stiffeners for enhancing the shear capacity of slender plates at ambient and elevated temperatures. Specifically, evaluations are made regarding the effectiveness of stiffeners for increasing the shear buckling capacity through various stiffener orientations, providing lateral restraint, and providing a load path for shear forces. In particular, the elastic shear buckling load, Vcr, and the ultimate shear postbuckling load, Vu, of the steel plate are examined. Finite element analyses, which have been validated with experimental data, are used as a basis for the study. The temperatures studied range from ambient to 1100 °C. This study provides some important insights on the behavior of plates under shear loads. For example, results indicate that the stiffener's role is not that of a load path for the shear forces, but one of lateral restraint, regardless of its geometric orientation. Further, it is shown that for lower temperatures a stiffener oriented along the compression diagonal (opposite to a tension field) provides the most improvement in postbuckling strength.